Virginia Woolf
214 p.
Keywords: This volume covers a wide range of editorial confrontations with Virginia Woolf's writings, touching on almost every genre in which she wrote: fiction, diary, letter, biography. It describes a variety of editorial practices and deals with current theories informing the critical editing of the prose of this singular twentieth-century woman writer. This collections of essays by distinguished scholar-critics of Virginia Woof confronts a number of contemporary issues in critical editing: the use of pre-print materials, authorial revision, the collation of historical texts; and it engages in a lively discussion of the present-day editorial apparatus, tackling questions on annotation and paratext. The volume is essential reading for anyone seriously interested in the critical editing of Modernist writing or in the ways in which Woolf's canon has been and is being preserved for her present and future readers.